2020
DOI: 10.1080/1351847x.2020.1772335
|View full text |Cite
|
Sign up to set email alerts
|

Fintech, financial inclusion and income inequality: a quantile regression approach

Abstract: Although theory suggests that financial market imperfections-mainly information asymmetries, market segmentation and transaction costs-prevent poor people from escaping poverty by limiting their access to formal financial services, new financial technologies (FinTech) are seen as key enablers of financial inclusion. Indeed, the UN 2030 Agenda for Sustainable Development (UN-2030-ASD) and the G20 High-Level Principles for Digital Financial Inclusion (G20-HLP-DFI) highlight the importance of harnessing the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
180
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(204 citation statements)
references
References 83 publications
14
180
0
10
Order By: Relevance
“…Moreover, it has a greater impact when individuals have access to digital financial services (i.e., mobile money) (Iqbal et al, 2020 ) Bangladesh 2010–2015 Population in moderate and extreme poverty (%) Branches per 10 km2; accounts per adult; deposits per adult; credit per adult; river erosion; cropping intensity; paved road; high remittance By using a unique dataset of 544 administrative sub districts of Bangladesh, the authors found that financial inclusion decreases both extreme and moderate poverty levels in rural areas (Mushtaq & Bruneau, 2019 ) 62 countries 2001–2012 Poverty headcount ratio; Gini index; Poverty gap; GDP per capita Deposits per head; Borrower ratio; Loans (% GDP); GDP per capita; trade openness; government consumption; inflation; mobile; fixed telephone; internet; price of 3-min local call Results suggest financial inclusion had negative and significant effects on poverty and inequality. Moreover, Information and Communication Technologies (ICT) stimulate financial inclusion, therefore favoring economic growth and reducing poverty and inequality (Demir et al, 2020 ) 140 countries 2011, 2014 and 2017 Gini index Use of mobile phone to pay bills (% population); Accounts (% population); Savings (% population); Borrowers (% population); GDP growth; education; trade openness; government expenditure; inflation; population Financial inclusion reduces inequality at all quantiles of the inequality distribution, and 'FinTech' also reduces income inequality (Park & Mercado, 2017 ) 176 countries 2004–2012 Poverty headcount ratio; Gini index ATMs per 100,000 adults; branches per 100,000 adults; borrowers per 1000 adults; credit (% GDP); depositors per 1000 adults; share of highest to lowest income; inflation; education; banks growth; GDP growth; Rule of Law Results demonstrate that financial inclusion is capable of decreasing poverty and inequality levels. However, financial inclusion presented no effect on inequality when only a subsample of 37 developing Asian nations was considered (Fouejieu et al, 2020 ) Between 19 and 107 countries 2004–2015 Gini index ATMs per 100,000 adults; number of bank branches per 100,000 adults; number of ...…”
Section: Financial Inclusion and Its Impact On Poverty And Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has a greater impact when individuals have access to digital financial services (i.e., mobile money) (Iqbal et al, 2020 ) Bangladesh 2010–2015 Population in moderate and extreme poverty (%) Branches per 10 km2; accounts per adult; deposits per adult; credit per adult; river erosion; cropping intensity; paved road; high remittance By using a unique dataset of 544 administrative sub districts of Bangladesh, the authors found that financial inclusion decreases both extreme and moderate poverty levels in rural areas (Mushtaq & Bruneau, 2019 ) 62 countries 2001–2012 Poverty headcount ratio; Gini index; Poverty gap; GDP per capita Deposits per head; Borrower ratio; Loans (% GDP); GDP per capita; trade openness; government consumption; inflation; mobile; fixed telephone; internet; price of 3-min local call Results suggest financial inclusion had negative and significant effects on poverty and inequality. Moreover, Information and Communication Technologies (ICT) stimulate financial inclusion, therefore favoring economic growth and reducing poverty and inequality (Demir et al, 2020 ) 140 countries 2011, 2014 and 2017 Gini index Use of mobile phone to pay bills (% population); Accounts (% population); Savings (% population); Borrowers (% population); GDP growth; education; trade openness; government expenditure; inflation; population Financial inclusion reduces inequality at all quantiles of the inequality distribution, and 'FinTech' also reduces income inequality (Park & Mercado, 2017 ) 176 countries 2004–2012 Poverty headcount ratio; Gini index ATMs per 100,000 adults; branches per 100,000 adults; borrowers per 1000 adults; credit (% GDP); depositors per 1000 adults; share of highest to lowest income; inflation; education; banks growth; GDP growth; Rule of Law Results demonstrate that financial inclusion is capable of decreasing poverty and inequality levels. However, financial inclusion presented no effect on inequality when only a subsample of 37 developing Asian nations was considered (Fouejieu et al, 2020 ) Between 19 and 107 countries 2004–2015 Gini index ATMs per 100,000 adults; number of bank branches per 100,000 adults; number of ...…”
Section: Financial Inclusion and Its Impact On Poverty And Inequalitymentioning
confidence: 99%
“…Granting that developed economies present high levels of financial inclusion, the overall status of financial inclusion (and its efficiency) in developing nations is still under discussion (Donou-Adonsou & Sylwester, 2016 ; Park & Mercado, 2017 ; Swamy, 2014 ). Many studies already found empirical evidence of financial inclusion benefiting the poor (Demir et al, 2020 ; Fouejieu et al, 2020 ; Koomson et al, 2020 ; Mushtaq & Bruneau, 2019 ; N'Dri & Kakinaka, 2020 ; Omar & Inaba, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…They found that, despite signi cant development in China's nancial system, there is still a development inequality between the most and least developed regions. Some of the previous studies have used World Bank ndex data to examine the relationship of demographic characteristics with accessibility and usage of digital nancial services (Anson et al, 2013;Borg & Smith, 2018;Demir et al, 2020;Demirguc-Kunt & Klapper, 2012, 2013Efobi et al, 2014;Zins and Weill, 2016). For instance, Anson et al, (2013) used data from the Global Financial Inclusion Indicators (Global Findex) database and attempted to study account ownership patterns at post o ces in comparison to traditional nancial institutions such as banks.…”
Section: Studies On Determinants Of Digital Nancial Services In Globamentioning
confidence: 99%
“…Besides, other non-demographic factor such as attitude, access, and digital self-e cacy are also determines how people engage with internet use to address digital inclusion. Demir et al (2020) investigated the interrelationship among nancial technology (FinTech), nancial inclusion and income inequality for a panel of 140 countries across the globe. The ndings of the study show that FinTech and nancial inclusion signi cantly reduces income inequality and these in uences are primarily concern with the higher-income countries.…”
Section: Studies On Determinants Of Digital Nancial Services In Globamentioning
confidence: 99%
“…Digital finance may complement traditional financial intermediaries by increasing access to finance for the members of the population who are often underserved or ignored by inefficient Chinese formal institutions. Consequently, digital finance might create more opportunities to improve income equality and social welfare (Cocco, Gomes, and Maenhout 2005;Demir et al 2020). Next, by competing with traditional finance business, digital finance may also enhance the resilience of a financial system and promote financial stability (Buchak et al 2018).…”
Section: Introductionmentioning
confidence: 99%